History, Power, Text Cultural Studies and Indigenous Studies - Neale, Timothy; McKinnon, Crystal; Vincent, Eve (UTS ePRESS, 2014)
History, Power, Text: Cultural Studies and Indigenous Studies is a collection of essays on Indigenous themes published between 1996 and 2013 in the journal known first as UTS Review and now as Cultural Studies Review. This journal opened up a space for new kinds of politics, new styles of writing and new modes of interdisciplinary engagement. History, Power, Text highlights the significance of just one of the exciting interdisciplinary spaces, or meeting points, the journal enabled. 'Indigenous cultural studies' is our name for the intersection of cultural studies and Indigenous studies showcased here. This volume republishes key works by academics and writers Katelyn Barney, Jennifer Biddle, Tony Birch, Wendy Brady, Gillian Cowlishaw, Robyn Ferrell, Bronwyn Fredericks, Heather Goodall, Tess Lea, Erin Manning, Richard Martin, Aileen Moreton-Robinson, Stephen Muecke, Alison Ravenscroft, Deborah Bird Rose, Lisa Slater, Sonia Smallacombe, Rebe Taylor, Penny van Toorn, Eve Vincent, Irene Watson and Virginia Watson-many of whom have taken this opportunity to write reflections on their work-as well as interviews between Christine Nicholls and painter Kathleen Petyarre, and Anne Brewster and author Kim Scott. The book also features new essays by Birch, Moreton-Robinson and Crystal McKinnon, and a roundtable discussion with former and current journal editors Chris Healy, Stephen Muecke and Katrina Schlunke.